Dental Composition
The dental composition addresses the issues of adhesion, mechanical strength, and polymerization shrinkage stress in self-adhesive dental resins by using specific (meth)acrylic compounds and monomers, enhancing performance in deep cavities.
Patent Information
- Application Number
- JP2021551692
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-08
- Filing Date
- 2020-10-07
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-10-07
AI Technical Summary
Existing self-adhesive dental composite resins lack sufficient adhesion, mechanical strength, and exhibit high polymerization shrinkage stress, particularly in deep cavities.
A dental composition comprising a (meth)acrylic compound with a weight average molecular weight of 5,000 to 50,000, a monomer with an acidic group of less than 5,000, and a monomer without an acidic group, along with a polymerization initiator, to reduce polymerization shrinkage stress while maintaining adhesion and mechanical strength.
The dental composition achieves excellent adhesiveness to tooth substance, high mechanical strength, and low polymerization shrinkage stress, reducing the risk of detachment and marginal leakage even in deep cavities.
Smart Images

Figure 0007606466000001 
Figure 0007606466000002 
Figure 0007606466000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental composition for use in the dental medical field. [Background technology]
[0002] In the treatment of dental caries and the associated defects, restoration using dental bonding material and dental composite resin has been commonly used. The restorative treatment is carried out in the following procedure. First, the carious part is removed to form a cavity, and then dental bonding material is applied to the cavity, and then the area where the dental bonding material was applied is irradiated with visible light to harden it. Next, dental composite resin is filled on top of the hardened dental bonding material layer, and finally the filled dental composite resin is irradiated with visible light to harden it.
[0003] The above-mentioned restorative method uses two materials: dental bonding material and dental composite resin. Recently, however, a self-adhesive dental composite resin, which is a dental composite resin with adhesive properties, has been developed and is now being used as a material that eliminates the need for dental bonding material and simplifies the operational steps of restorative treatment.
[0004] Self-adhesive dental composite resins contain, in addition to the components of conventional dental composite resins, namely polyfunctional monomers and fillers whose main purpose is to impart high mechanical strength to the cured product, and polymerization initiators whose main purpose is to improve the curing properties, monomers having acidic groups that have traditionally been used in dental bonding materials to impart adhesion to tooth structure (see, for example, Patent Documents 1 and 2).
[0005] As the polyfunctional monomer, a polyfunctional (meth)acrylate is generally used. For example, Patent Document 1 describes that in addition to the use of a polyfunctional monomer having a main skeleton of a sugar alcohol or the like, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, polyethylene glycol di(meth)acrylate, etc. may be used. Patent Document 2 also describes that a monomer having at least two ethylenically unsaturated groups, such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, etc., may be used. For the purpose of imparting high mechanical strength, it is common to use a polyfunctional monomer having a relatively small molecular weight in order to increase the density of the polymerizable group. In Patent Document 2, the molecular weight of the monomer having at least two ethylenically unsaturated groups used is within the range of 270 to 900. Patent Document 1 also describes that, with regard to 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, one having an average polymerization degree of oxyethylene chains of 1 to 4 is particularly used, and the 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane used in the examples has an average of 2.6 oxyethylene chains per molecule.
[0006] In addition, it is generally known that compositions containing monomers such as (meth)acrylic monomers, such as dental composite resins, shrink in volume due to polymerization shrinkage when polymerized and cured. In conventional dental restorative treatment using a dental bonding material and a dental composite resin, stress (hereinafter sometimes referred to as polymerization shrinkage stress) generated by volume shrinkage when polymerizing and curing the dental composite resin is concentrated at the adhesive interface between the tooth substance and the dental bonding material, and the polymerization shrinkage stress may cause marginal leakage or loss of the restoration, but in recent years, the performance of dental bonding materials has improved and these clinical problems have been decreasing.
[0007] However, when the compositions described in Patent Documents 1 and 2 are applied directly to tooth structure as a self-adhesive dental composite resin without using a dental bonding material, the adhesion to tooth structure and mechanical strength are good, but the polymerization shrinkage stress has not been taken into consideration. Therefore, the inventors have found that there is room for improvement in terms of the polymerization shrinkage stress.
[0008] For example, a self-adhesive dental composite resin that combines high adhesion to tooth structure, high mechanical strength, and low polymerization shrinkage stress has been proposed by using a specific amount of a long-chain polyfunctional monomer with a specific structure to reduce polymerization shrinkage stress (Patent Document 3). However, as a result of the inventors' investigation, although the polymerization shrinkage stress in Patent Document 3 was certainly reduced compared to the conventional technology at that time, there was room for further improvement in polymerization shrinkage stress in consideration of the risk of detachment and marginal leakage when applied to cases where the influence of polymerization shrinkage stress is large, such as relatively deep cavities.
[0009] On the other hand, dental compositions containing oligomers are known (for example, Patent Documents 4 to 7). However, in Patent Documents 4 to 6, the oligomers are blended with the intention of improving mechanical strength, and there is no idea of reducing polymerization shrinkage stress. In addition, the present inventors have investigated the effect of reducing the polymerization shrinkage stress as desired.
[0010] On the other hand, Patent Document 7 describes a dental filling and restoration kit containing a specific amount of an unsaturated urethane oligomer having a weight-average molecular weight in the range of 1000 to 50000. However, the dental filling and restoration kit does not contain an acidic monomer and does not have adhesiveness to tooth structure. In addition, the inventors of the present invention have investigated the kit and found that it does not have the desired effect of reducing polymerization shrinkage stress. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2008-260752 A [Patent Document 2] European Patent Application Publication No. 2153811 [Patent Document 3] JP 2012-171885 A [Patent Document 4] Japanese Patent Application Publication No. 50-042696 [Patent Document 5] Special Publication No. 2006-510583 [Patent Document 6] JP 2009-184971 A [Patent Document 7] JP 2011-144121 A Summary of the Invention [Problem to be solved by the invention]
[0012] Thus, in the prior art, a self-adhesive dental composite resin that is excellent in all respects of adhesion to tooth structure, mechanical strength, and polymerization shrinkage stress has not been found.
[0013] Therefore, an object of the present invention is to provide a dental composition which has excellent adhesion to tooth structure, excellent mechanical strength of the cured product, and low polymerization shrinkage stress. [Means for solving the problem]
[0014] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a specific (meth)acrylic compound, and have completed the present invention after further investigations.
[0015] That is, the present invention provides [1] A dental composition comprising: a (meth)acrylic compound (A) having a weight-average molecular weight of 5,000 to 50,000; a monomer (B) having an acidic group and a molecular weight of less than 5,000; a monomer (C) having no acidic group and a molecular weight of less than 5,000; and a polymerization initiator (D), wherein the weight-average molecular weight per (meth)acrylic group of the (meth)acrylic compound (A) is 1,250 or more and less than 20,000; [2] The dental composition according to [1], wherein the (meth)acrylic compound (A) is a urethane-modified (meth)acrylic compound (A-1); [3] The dental composition according to [1] or [2], wherein the content of the (meth)acrylic compound (A) is 0.1 to 30 parts by mass per 100 parts by mass in total of the (meth)acrylic compound (A), the monomer (B) having an acidic group, and the monomer (C) not having an acidic group; [4] The dental composition according to any one of [1] to [3], wherein the (meth)acrylic compound (A) has a viscosity at 25°C of 5,000 cps or more; [5] The dental composition according to any one of [1] to [4], wherein the (meth)acrylic compound (A) has a glass transition temperature (Tg) of 20° C. or lower; [6] The dental composition according to any one of [1] to [5], wherein the (meth)acrylic compound (A) has a weight average molecular weight per (meth)acrylic group of 6,100 or more and less than 20,000; [7] The dental composition according to any one of [2] to [6], wherein the urethane-modified (meth)acrylic compound (A-1) is a (meth)acrylate having a urethane bond and a structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene; [8] The dental composition according to any one of [1] to [7], wherein the monomer (B) having an acidic group and a molecular weight of less than 5,000 contains a phosphate group-containing monomer; [9] The dental composition according to any one of [1] to [8], wherein the monomer (C) having no acidic group and having a molecular weight of less than 5,000 contains a hydrophobic monomer (C-1) having no acidic group and having a molecular weight of less than 5,000;
[10] The dental composition according to [9], wherein the hydrophobic monomer (C-1) having no acidic group and having a molecular weight of less than 5,000 contains an aliphatic compound-based bifunctional monomer;
[11] The dental composition according to any one of [1] to
[10] , wherein the polymerization initiator (D) contains a water-soluble photopolymerization initiator (D-1) having a solubility in water at 25°C of 10 g / L or more and a water-insoluble photopolymerization initiator (D-2) having a solubility in water at 25°C of less than 10 g / L;
[12] A self-adhesive dental composite resin comprising the dental composition according to any one of [1] to
[11] ;
[13] A dental bonding material comprising the dental composition according to any one of [1] to
[11] ;
[14] A dental cement comprising the dental composition according to any one of [1] to
[11] ; Includes: Effect of the Invention
[0016] According to the present invention, a dental composition is provided that has excellent adhesion to tooth structure, excellent mechanical strength of the cured product, and small polymerization shrinkage stress. Due to its characteristics, the dental composition is suitable for use in a self-adhesive dental composite resin, a dental bonding material, a dental cement, etc. In particular, according to the present invention, a self-adhesive dental composite resin, a dental bonding material, or a dental cement that can reduce the risk of detachment, marginal leakage, etc., even when applied to a case where the influence of polymerization shrinkage stress is large, such as a relatively deep cavity, can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The dental composition of the present invention includes, as essential components, a (meth)acrylic compound (A) having a weight average molecular weight of 5,000 to 50,000, a monomer (B) having an acidic group and a molecular weight of less than 5000, a monomer (C) having no acidic group and a molecular weight of less than 5000, and a polymerization initiator (D), and the weight average molecular weight per (meth)acrylic group of the (meth)acrylic compound (A) is 1,250 or more and less than 20,000. In this specification, (meth)acrylic is a general term for methacryl and acrylic, and the same applies to similar expressions. In this specification, the upper and lower limits of the numerical ranges (contents of each component, values calculated from each component, and each physical property, etc.) can be appropriately combined.
[0018] The reason why the dental composition of the present invention has excellent adhesion to tooth structure, excellent mechanical strength of the cured product, and small polymerization shrinkage stress is not clear, but it is presumed as follows. That is, it is presumed that the incorporation of the (meth)acrylic compound (A) relieves the stress generated during polymerization shrinkage. With only a low molecular weight monomer, the curability is very high, but the crosslink density is also high, and the polymerization shrinkage rate is also high. As a result, the shrinkage stress generated during polymerization is inevitably large. In the present invention, by using a (meth)acrylic compound (A) having a relatively large molecular weight and a ratio of the molecular weight to the polymerizable group within a specific range, the crosslink density in the polymer matrix is appropriately low, and it is considered that the stress applied during polymerization is significantly relieved while maintaining the mechanical strength. As a result, it is considered that the dental composition of the present invention has high adhesive strength even under conditions assuming cases where polymerization shrinkage stress is greatly affected, such as restorative treatment for a relatively deep cavity.
[0019] Each component used in the dental composition of the present invention will be described below.
[0020] [(Meth)acrylic compound (A) having a weight average molecular weight of 5,000 to 50,000] The (meth)acrylic compound (A) having a weight average molecular weight of 5,000 to 50,000 (hereinafter referred to as (meth)acrylic compound (A)) is used in the dental composition of the present invention in order to impart low polymerization shrinkage stress and high adhesive strength.
[0021] The (meth)acrylic compound (A) can be roughly classified into two types: urethane-modified (meth)acrylic compound (A-1) and (meth)acrylic compound without urethane bond. In terms of ease of introduction of (meth)acrylic group and effect of reducing polymerization shrinkage stress, the urethane-modified (meth)acrylic compound (A-1) is preferred. The urethane-modified (meth)acrylic compound (A-1) can be easily synthesized, for example, by addition reaction of a polyol containing a polymer skeleton described later, a compound having an isocyanate group (-NCO), and a (meth)acrylic compound having a hydroxyl group (-OH). The urethane-modified (meth)acrylic compound (A-1) can be easily synthesized by ring-opening addition reaction of a (meth)acrylic compound having a hydroxyl group with lactone or alkylene oxide, and then addition reaction of the resulting compound having a hydroxyl group at one end with a compound having an isocyanate group. The (meth)acrylic compound that imparts a (meth)acrylic group to a polymer can be, for example, introduced into a polymer of a monomer having a hydroxyl group by a dehydration condensation reaction of (meth)acrylic acid. The (meth)acrylic compound (A) may be used alone or in combination of two or more kinds.
[0022] · Urethane (meth)acrylic compound (A-1) The urethanized (meth)acrylic compound (A-1) is preferably a (meth)acrylate having, in addition to a urethane bond, a structure (polymer skeleton) selected from the group consisting of polyesters, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes, and more preferably a (meth)acrylate having at least one polyol moiety selected from the group consisting of polyesters, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes having a structure derived from an aliphatic diol unit having 4 to 18 carbon atoms and a branched structure in the molecule, and a urethane bond. These are not particularly limited as long as they have the above structure. For example, examples of polyesters include polymers of dicarboxylic acids (aromatic dicarboxylic acids such as phthalic acid and isophthalic acid; unsaturated aliphatic dicarboxylic acids such as maleic acid) and aliphatic diols having 2 to 18 carbon atoms, polymers of dicarboxylic acids (saturated aliphatic dicarboxylic acids such as adipic acid and sebacic acid) and aliphatic diols having 2 to 18 carbon atoms, polymers of β-propiolactone, polymers of γ-butyrolactone, polymers of δ-valerolactone, polymers of ε-caprolactone, and copolymers thereof. Of these, polymers of dicarboxylic acids (aromatic dicarboxylic acids such as phthalic acid and isophthalic acid; unsaturated aliphatic dicarboxylic acids such as maleic acid) and aliphatic diols having 2 to 12 carbon atoms, and polymers of dicarboxylic acids (saturated aliphatic dicarboxylic acids such as adipic acid and sebacic acid) and aliphatic diols having 2 to 12 carbon atoms are preferred. Examples of the polycarbonate include polycarbonates derived from an aliphatic diol having 2 to 18 carbon atoms, polycarbonates derived from bisphenol A, and polycarbonates derived from an aliphatic diol having 2 to 18 carbon atoms and bisphenol A, and preferred are polycarbonates derived from an aliphatic diol having 2 to 12 carbon atoms, polycarbonates derived from bisphenol A, and polycarbonates derived from an aliphatic diol having 2 to 12 carbon atoms and bisphenol A. Examples of the polyurethane include polymers of an aliphatic diol having 2 to 18 carbon atoms and a diisocyanate having 1 to 18 carbon atoms, and preferred are polymers of an aliphatic diol having 2 to 12 carbon atoms and a diisocyanate having 1 to 12 carbon atoms.Examples of polyethers include polyethylene glycol, polypropylene glycol, polybutylene glycol, and poly(1-methylbutylene glycol). Examples of polyconjugated dienes and hydrogenated polyconjugated dienes include 1,4-polybutadiene, 1,2-polybutadiene, polyisoprene, poly(butadiene-isoprene), poly(butadiene-styrene), poly(isoprene-styrene), polyfarnesene, and hydrogenated products thereof. Among these, the structures of polyester, polycarbonate, and polyconjugated diene are preferred in terms of excellent mechanical strength and water resistance. The polyol having the above-mentioned polymer skeleton can be used to produce the urethane-modified (meth)acrylic compound (A-1).
[0023] Examples of compounds having an isocyanate group include hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), trimethylhexamethylene diisocyanate (TMHMDI), tricyclodecane diisocyanate (TCDDI), and adamantane diisocyanate (ADI).
[0024] Examples of the (meth)acrylic compound having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin mono(meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl (meth)acrylate. hydroxy(meth)acrylate compounds such as dipentaerythritol tri(meth)acrylate, 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri- or tetra(meth)acrylate; and hydroxy(meth)acrylamide compounds such as N-hydroxyethyl(meth)acrylamide and N,N-bis(2-hydroxyethyl)(meth)acrylamide.
[0025] Examples of the aliphatic diol having 4 to 18 carbon atoms and a branched structure include 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 1,3-butanediol, 2-methyl-1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 2,7-dimethyl-1,8-octanediol, 2-methyl-1,9-nonanediol, 2,8-dimethyl-1,9-nonanediol, 2-methyl-1,10-decanediol, 2,9-dimethyl-1,10-decanediol, and 2-methyl-1,11-undecandiol. Examples of the dimethyl-1,15-pentadecanediol include 2,14-dimethyl-1,15-pentadecanediol, 2,14-dimethyl-1,15-pentadecanediol, 2-methyl-1,16-hexadecanediol, and 2,15-dimethyl-1,16-hexadecanediol. Among these, from the viewpoint of excellent hardening properties of the dental composition, it is preferable to use an aliphatic diol having 5 to 12 carbon atoms and a methyl group as a side chain, such as 2-methyl-1,4-butanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 2,7-dimethyl-1,8-octanediol, 2-methyl-1,9-nonanediol, or 2,8-dimethyl-1,9-nonanediol, as the polyol component, more preferably 2-methyl-1,4-butanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, or 2,7-dimethyl-1,8-octanediol, and even more preferably 3-methyl-1,5-pentanediol or 2-methyl-1,8-octanediol.
[0026] The addition reaction between a compound having an isocyanate group and a (meth)acrylic compound having a hydroxyl group can be carried out according to a known method, and there is no particular limitation.
[0027] The obtained urethane-modified (meth)acrylic compound (A-1) may be a reaction product of any combination of a polyol having at least one structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene, a compound having an isocyanate group, and a (meth)acrylic compound having a hydroxyl group.
[0028] The weight average molecular weight (Mw) of the (meth)acrylic compound (A) is 5,000 to 50,000, preferably 6,000 to 30,000, and more preferably 7,500 to 20,000, from the viewpoint of viscosity and reduction of polymerization shrinkage stress. In one embodiment of the present invention, the weight average molecular weight (Mw) of the (meth)acrylic compound (A) is preferably 12,100 to 50,000, more preferably 12,500 to 30,000, and even more preferably 12,500 to 20,000. The weight average molecular weight (Mw) in the present invention means a weight average molecular weight calculated in terms of polystyrene obtained by gel permeation chromatography (GPC).
[0029] If the number of (meth)acrylic groups, which are polymerizable groups of the (meth)acrylic compound (A), is too large, the crosslink density becomes high, and the polymerization shrinkage stress cannot be sufficiently reduced. On the other hand, if the number of (meth)acrylic groups is too small, the crosslink density becomes low, and the mechanical strength decreases. Therefore, the weight average molecular weight per (meth)acrylic group in the (meth)acrylic compound (A) is 1,250 or more and less than 20,000, preferably 1,500 or more and less than 17,500, more preferably 1,800 or more and less than 16,000, and even more preferably 2,500 or more and less than 15,000. In one embodiment of the present invention, the weight average molecular weight per (meth)acrylic group in the (meth)acrylic compound (A) is 6,100 or more and less than 20,000, preferably 6,200 or more and less than 17,500, more preferably 6,250 or more and less than 16,000, and even more preferably 6,500 or more and less than 15,000. Furthermore, when the (meth)acrylic compound (A) contains a polymerizable group other than the (meth)acrylic group, such as a vinyl group or a styrene group, the polymerization shrinkage stress may become large depending on the polymerization form. Therefore, the number of polymerizable groups other than the (meth)acrylic group in the (meth)acrylic compound (A) is preferably 2 or less, and the number of polymerizable groups is more preferably 0.
[0030] From the viewpoint of reducing polymerization shrinkage stress, the glass transition temperature (Tg) of the (meth)acrylic compound (A) is preferably -100°C or more and 20°C or less, more preferably -75°C to 15°C, and even more preferably -60°C to 10°C. The glass transition temperature (Tg) of the (meth)acrylic compound (A) can be measured by a conventional method using a viscoelasticity measuring device (rheometer), a differential scanning calorimeter (DSC), or the like. For example, the glass transition temperature (Tg) can be determined by performing dynamic viscoelasticity measurement of the (meth)acrylic compound (A) using a rotational rheometer (manufactured by TA Instruments Japan, "AR2000"), and in this dynamic viscoelasticity measurement, the frequency is set to 10Hz, the load is set to 10N, the displacement is set to 0.1%, and the torque is set to 20μNm, and the temperature at which tanδ reaches a peak can be determined as the glass transition temperature Tg.
[0031] The viscosity of the (meth)acrylic compound (A) at 25°C is preferably 5,000 to 10,000,000 cps, more preferably 10,000 to 7,500,000 cps, and even more preferably 20,000 to 7,000,000 cps, from the viewpoints of operability and reduction of polymerization shrinkage stress. The viscosity in the present invention means the viscosity measured by a Brookfield viscometer at 25°C. The measurement conditions such as time and rotation speed are appropriately adjusted depending on the viscosity range.
[0032] As the (meth)acrylic compound (A), a commercially available product may be used. Commercially available products include, for example, the "Art Resin" series manufactured by Negami Chemical Industries Co., Ltd. (UN-350, UN-353, UN-7700, UN-1255 (viscosity: >2,000,000cps / 25°C, weight average molecular weight (Mw): 8,000, glass transition temperature (Tg): -14°C, number of acrylic groups: 2), UN-6200 (viscosity: 15,000 to 40,000cps, weight average molecular weight (Mw): 6,500, glass transition temperature (Tg): -52°C, polyether skeleton, number of acrylic groups: 2), UN-6202 (viscosity: 7,000 to 23,000cps / 25°C, weight average molecular weight (Mw): 11,000, glass transition temperature (Tg): -41°C, polyether skeleton, number of acrylic groups: 2), UN-6204 (viscosity: >200,000cps / 25°C, weight average molecular weight (Mw): 11,000, glass transition temperature (Tg): -41°C, polyether skeleton, number of acrylic groups: 2), ℃, weight average molecular weight (Mw): 13,000, glass transition temperature (Tg): -74 ° C, polyether skeleton, number of acrylic groups: 2), UN-6205 (viscosity: > 1,600,000 cps / 25 ° C, weight average molecular weight (Mw): 27,000, glass transition temperature (Tg): -74 ° C, polyether skeleton, number of acrylic groups: 2), UN-9000PEP (viscosity: > 2,000,000 cps / 25 ° C, weight average molecular weight (Mw): 5,000, glass transition temperature (Tg): -7 ° C, polycarbonate skeleton, number of acrylic groups: 2), UN-9000A (viscosity: > 2,000,000 cps / 25 ° C, weight average molecular weight (Mw): 15,000, glass transition temperature (Tg): -27 ° C, polycarbonate skeleton, number of acrylic groups: 2)).
[0033] The content of the (meth)acrylic compound (A) in the dental composition of the present invention is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 25 parts by mass, and even more preferably 1 to 20 parts by mass, per 100 parts by mass in total of the (meth)acrylic compound (A), the monomer (B) having an acidic group and having a molecular weight of less than 5,000, and the monomer (C) having no acidic group and having a molecular weight of less than 5,000, from the viewpoints of mechanical strength, paste properties, and reduction of polymerization shrinkage stress.
[0034] [Monomer (B) having an acidic group and a molecular weight of less than 5000] Monomer (B) having an acidic group and a molecular weight of less than 5000 (hereinafter referred to as monomer (B) having an acidic group) has an acid etching effect and a primer treatment effect, and is a component that imparts demineralizing and penetrating effects. Monomer (B) having an acidic group is also polymerizable, and also imparts a hardening effect. By including monomer (B) having an acidic group, the adhesion to tooth structure and the adhesion durability are improved.
[0035] Examples of the monomer (B) having an acidic group include monomers having at least one acidic group such as a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, or a carboxylic acid group, and at least one polymerizable group such as a (meth)acryloyl group, a vinyl group, or a styrene group. From the viewpoint of adhesion to tooth structure, a monomer containing a phosphoric acid group is preferable. Specific examples of the monomer (B) having an acidic group are given below.
[0036] Examples of the phosphate group-containing monomer include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyethyl dihydrogen phosphate, 9-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxyethyl dihydrogen phosphate, 11-(meth)acryloyloxyethyl dihydrogen phosphate, 12-(meth)acryloyloxyethyl dihydrogen phosphate, 13-(meth)acryloyloxyethyl dihydrogen phosphate, 14-(meth)acryloyloxyethyl dihydrogen phosphate, 15-(meth)acryloyloxyethyl dihydrogen phosphate, 16-(meth)acryloyloxyethyl dihydrogen phosphate, 17-(meth)acryloyloxyethyl dihydrogen phosphate, 18-(meth)acryloyloxyethyl dihydrogen phosphate, 19-(meth)acryloyloxyethyl dihydrogen phosphate, 20-(meth)acryloyloxyethyl dihydrogen phosphate, 21-(meth)acryloyloxyethyl dihydrogen phosphate, 22-(meth)acryloyloxyethyl dihydrogen phosphate, 23-(meth)acryloyloxyethyl dihydrogen phosphate, 24-(meth)acryloyloxyethyl dihydrogen phosphate, 25-(meth)acryloyloxyethyl dihydrogen phosphate, 26-(meth)acryloyloxyethyl dihydrogen phosphate, 27-(meth)acryloyloxyethyl dihydrogen phosphate, 28-(meth)acryloyl Acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyicosyl dihydrogen phosphate hydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, bis[4-(meth)acryloyloxybutyl]hydrogen phosphate, bis[6-(meth)acryloyloxyhexyl]hydrogen phosphate, bis[8-(meth)acryloyloxyoctyl]hydrogen phosphate, bis[9-(meth)acryloyloxynonyl]hydrogen phosphate, bis[10-(meth)acryloyloxydecyl]hydrogen Examples of the phosphate-containing (meth)acrylic monomers include phosphate, 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-2-bromoethyl hydrogen phosphate, bis[2-(meth)acryloyloxy-(1-hydroxymethyl)ethyl]hydrogen phosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0037] Examples of the pyrophosphate group-containing monomer include bis[2-(meth)acryloyloxyethyl]pyrophosphate, bis[4-(meth)acryloyloxybutyl]pyrophosphate, bis[6-(meth)acryloyloxyhexyl]pyrophosphate, bis[8-(meth)acryloyloxyoctyl]pyrophosphate, bis[10-(meth)acryloyloxydecyl]pyrophosphate, and acid chlorides, alkali metal salts, ammonium salts, and other pyrophosphate group-containing (meth)acrylic monomers.
[0038] Examples of the thiophosphate group-containing monomer include 2-(meth)acryloyloxyethyl dihydrogenthiophosphate, 3-(meth)acryloyloxypropyl dihydrogenthiophosphate, 4-(meth)acryloyloxybutyl dihydrogenthiophosphate, 5-(meth)acryloyloxypentyl dihydrogenthiophosphate, 6-(meth)acryloyloxyhexyl dihydrogenthiophosphate, 7-(meth)acryloyloxyheptyl dihydrogenthiophosphate, and 8-(meth)acryloyloxyoctyl dihydrogenthiophosphate. Examples of suitable acryloyloxyalkyl groups include acryloyloxyalkyl phosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate, 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0039] Examples of the phosphonic acid group-containing monomer include 2-(meth)acryloyloxyethyl phenyl phosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0040] Examples of the sulfonic acid group-containing monomer include 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, and 2-sulfoethyl (meth)acrylate.
[0041] Carboxylic acid group-containing monomers include monomers having one carboxy group in the molecule and monomers having multiple carboxy groups in the molecule.
[0042] Examples of monomers having one carboxy group in the molecule include (meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, O-(meth)acryloyltyrosine, N-(meth)acryloyltyrosine, N-(meth)acryloylphenylalanine, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, p-vinylbenzoic acid, and 2-(meth)acryloyloxybenzoic acid. Examples of the acryloyloxyethyl group include aromatic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen maleate, and acid halides thereof.
[0043] Examples of monomers having multiple carboxy groups in the molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid, 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 4 ...4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyhexane Examples of the acid anhydride include 4-(meth)acryloyloxyethyl trimellitate, 4-(meth)acryloyloxyethyl trimellitate anhydride, 4-(meth)acryloyloxybutyl trimellitate, 4-(meth)acryloyloxyhexyl trimellitate, 4-(meth)acryloyloxydecyl trimellitate, 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate, and acid anhydrides or acid halides thereof.
[0044] Among these monomers (B) having an acidic group, phosphate or pyrophosphate group-containing (meth)acrylic monomers are preferred because they exhibit superior adhesiveness to tooth structure, and phosphate group-containing (meth)acrylic monomers are particularly preferred. Among these, divalent phosphate group-containing (meth)acrylic monomers having an alkyl or alkylene group with 6 to 20 carbon atoms as the main chain in the molecule are more preferred, and divalent phosphate group-containing (meth)acrylic monomers having an alkylene group with 8 to 12 carbon atoms as the main chain in the molecule, such as 10-methacryloyloxydecyl dihydrogen phosphate, are even more preferred, in that they exhibit high demineralization properties in the absence of organic solvents and high adhesiveness.
[0045] The monomer (B) having an acidic group may be used alone or in combination of two or more. When the content of the monomer (B) having an acidic group is either too much or too little, the adhesiveness may decrease. Therefore, the content of the monomer (B) having an acidic group is preferably in the range of 1 to 50 parts by mass, more preferably in the range of 3 to 40 parts by mass, and even more preferably in the range of 5 to 30 parts by mass, based on 100 parts by mass of the total amount of the polymerizable components in the dental composition.
[0046] The molecular weight of the monomer (B) having an acidic group is preferably 4,000 or less, more preferably 3,000 or less, and even more preferably 2,000 or less.
[0047] [Monomer (C) having no acidic group and having a molecular weight of less than 5000] Monomers (C) having no acidic group and a molecular weight of less than 5,000 (hereinafter referred to as monomers (C) having no acidic group) can be classified into hydrophobic monomers (C-1) having no acidic group and a molecular weight of less than 5,000 and hydrophilic monomers (C-2) having no acidic group and a molecular weight of less than 5,000.
[0048] Hydrophobic monomers (C-1) with no acidic groups and a molecular weight of less than 5,000 The hydrophobic monomer (C-1) having no acidic group and a molecular weight of less than 5000 (hereinafter referred to as hydrophobic monomer (C-1)) improves the mechanical strength, handling properties, etc. of the dental composition. A radical monomer having no acidic group and a polymerizable group is preferable, and from the viewpoint of easiness of radical polymerization, the polymerizable group is preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophobic monomer (C-1) means a monomer having a molecular weight of less than 5000 and a solubility in water at 25°C of less than 10% by mass, and examples of such monomers include crosslinkable monomers such as bifunctional monomers of aromatic compounds, bifunctional monomers of aliphatic compounds, and trifunctional or higher monomers.
[0049] Examples of the aromatic bifunctional monomer include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, and the like. phenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like. Among these, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (having an average added mole number of ethoxy groups of 2.6, commonly known as "D-2.6E"), 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane are preferred.
[0050] Examples of the aliphatic compound-based bifunctional monomer include glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)di(meth)acrylate, N-methacryloyloxyethylacrylamide, and N-methacryloyloxypropylamide. Among these, triethylene glycol diacrylate, triethylene glycol dimethacrylate (commonly known as "3G"), neopentyl glycol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl) dimethacrylate (commonly known as "UDMA"), 1,10-decanediol dimethacrylate (commonly known as "DD"), 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl) dimethacrylate, and N-methacryloyloxyethyl acrylamide (commonly known as "MAEA") are preferred.
[0051] Examples of trifunctional or higher monomers include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, 1,7-diacryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane, etc. Among these, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate is preferred.
[0052] Among the above hydrophobic monomers (C-1), from the viewpoint of mechanical strength and handling, aromatic compound-based bifunctional monomers and aliphatic compound-based bifunctional monomers are preferably used. As aromatic compound-based bifunctional monomers, Bis-GMA and D-2.6E are preferred. As aliphatic compound-based bifunctional monomers, glycerol di(meth)acrylate, 3G, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, DD, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, UDMA, and MAEA are preferred.
[0053] Among the above hydrophobic monomers (C-1), from the viewpoints of initial adhesive strength to tooth structure, adhesive durability, and mechanical strength, Bis-GMA, D-2.6E, 3G, UDMA, DD, and MAEA are more preferred, and D-2.6E, DD, and MAEA are even more preferred.
[0054] The hydrophobic monomer (C-1) may be used alone or in combination of two or more. If the content of the hydrophobic monomer (C-1) is too high, the composition may have a reduced permeability into the tooth structure and a reduced adhesive strength, and if the content is too low, the effect of improving the mechanical strength may not be sufficiently obtained. Therefore, the hydrophobic monomer (C-1) is preferably in the range of 20 to 99 parts by mass, more preferably in the range of 40 to 99 parts by mass, and even more preferably in the range of 60 to 99 parts by mass, based on 100 parts by mass of the total amount of the polymerizable components in the dental composition.
[0055] A hydrophilic monomer (C-2) having no acidic group and a molecular weight of less than 5,000 The dental composition of the present invention preferably further contains a hydrophilic monomer (C-2) having no acidic group and a molecular weight of less than 5000 (hereinafter referred to as hydrophilic monomer (C-2)). The hydrophilic monomer (C-2) promotes the penetration of the components of the dental composition into the tooth substance, and also penetrates into the tooth substance itself to adhere to the organic component (collagen) in the tooth substance. As the hydrophilic monomer (C-2), a radical monomer having no acidic group and a polymerizable group is preferable, and from the viewpoint of easy radical polymerization, the polymerizable group is preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophilic monomer (C-2) means a monomer having a molecular weight of less than 5000 and a solubility in water at 25°C of 10% by mass or more, preferably a monomer having a solubility of 30% by mass or more, and more preferably a monomer that can be dissolved in water at any ratio at 25°C. As the hydrophilic monomer (C-2), those having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, or an amide group are preferable. For example, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2-((meth)acryloyloxy)ethyl trimethylammonium chloride, polyethylene glycol di(meth)acrylate (those having 9 or more oxyethylene groups) are preferable. ); and monofunctional (meth)acrylamide monomers such as N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(2-hydroxyethyl) (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, 4-(meth)acryloylmorpholine, N-trihydroxymethyl-N-methyl (meth)acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide.
[0056] Among these hydrophilic monomers (C-2), from the viewpoint of adhesion to tooth structure, 2-hydroxyethyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, diacetone (meth)acrylamide and hydrophilic monofunctional (meth)acrylamide monomers are preferred, and 2-hydroxyethyl (meth)acrylate, N,N-dimethylacrylamide and N,N-diethylacrylamide are more preferred. One type of hydrophilic monomer (C-2) may be used alone, or two or more types may be used in combination.
[0057] In the present invention, if the content of the hydrophilic monomer (C-2) is too low, the effect of improving the adhesive strength may not be obtained sufficiently, and if it is too high, the mechanical strength may decrease. Therefore, the content of the hydrophilic monomer (C-2) is preferably in the range of 0 to 50 parts by mass, more preferably in the range of 0 to 40 parts by mass, and even more preferably in the range of 0 to 30 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable components in the dental composition. The content of the hydrophilic monomer (C-2) may be 0 parts by mass.
[0058] The molecular weight of the monomer (C) having no acidic group, whether it is a hydrophobic monomer (C-1) or a hydrophilic monomer (C-2), is preferably 4,000 or less, more preferably 3,000 or less, and even more preferably 2,000 or less.
[0059] [Polymerization initiator (D)] Polymerization initiators (D) are largely classified into photopolymerization initiators and chemical polymerization initiators, and photopolymerization initiators are further classified into water-soluble photopolymerization initiators (D-1) and water-insoluble photopolymerization initiators (D-2). As the polymerization initiator (D), only the water-soluble photopolymerization initiator (D-1) may be used, only the water-insoluble photopolymerization initiator (D-2) may be used, or the water-soluble photopolymerization initiator (D-1) and the water-insoluble photopolymerization initiator (D-2) may be used in combination.
[0060] Water-soluble photopolymerization initiator (D-1) The water-soluble photopolymerization initiator (D-1) improves polymerization curing at the hydrophilic tooth surface interface, and can realize high adhesive strength. The water-soluble photopolymerization initiator (D-1) has a solubility in water at 25°C of 10 g / L or more, preferably 15 g / L or more, more preferably 20 g / L or more, and even more preferably 25 g / L or more. If the solubility is less than 10 g / L, the water-soluble photopolymerization initiator (D-1) does not dissolve sufficiently in the water in the tooth substance at the adhesive interface, making it difficult to exhibit the polymerization promotion effect.
[0061] Examples of the water-soluble photopolymerization initiator (D-1) include water-soluble acylphosphine oxides, water-soluble thioxanthones, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one having a (poly)ethylene glycol chain introduced into the hydroxyl group, 1-hydroxycyclohexyl phenyl ketone having a (poly)ethylene glycol chain introduced into the hydroxyl group and / or phenyl group, 1-hydroxycyclohexyl phenyl ketone having -OCH2COO-Na+ introduced into the phenyl group, 2-hydroxy-2-methyl-1- Examples of such α-hydroxyalkylacetophenones include those in which a (poly)ethylene glycol chain has been introduced into the hydroxyl group and / or phenyl group of phenylpropan-1-one, and those in which -OCH2COO-Na+ has been introduced into the phenyl group of 2-hydroxy-2-methyl-1-phenylpropan-1-one; and those in which the amino group of α-aminoalkylphenones such as 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 has been converted into a quaternary ammonium salt.
[0062] Examples of the water-soluble thioxanthones include 2-hydroxy-3-(9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1-methyl-9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2- Hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, and the like can be used.
[0063] Examples of the water-soluble acylphosphine oxides include acylphosphine oxides represented by the following general formula (1) or (2).
[0064] [ka]
[0065] [ka]
[0066] In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 are each independently a linear or branched alkyl group having 1 to 4 carbon atoms or a halogen atom, and M is a hydrogen ion, an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN+ R 8 R 9 R 10 (In the formula, R 8 , R 9 , and R 10 are each independently an organic group or a hydrogen atom), n is 1 or 2, X is a linear or branched alkylene group having 1 to 4 carbon atoms, and R 7 -CH(CH3)COO(C2H4O) p It is represented by CH3, and p represents an integer of 1 to 1000.
[0067] R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 The alkyl group of R is not particularly limited as long as it is a straight or branched alkyl group having 1 to 4 carbon atoms, and examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a 2-methylpropyl group, and a tert-butyl group. 1 , R 2 , R 3 , R 4 , R 5 , and R 6 The alkyl group of X is preferably a linear alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and more preferably a methyl group. The alkylene group of X includes a methylene group, an ethylene group, an n-propylene group, an isopropylene group, and an n-butylene group. The alkylene group of X is preferably a linear alkylene group having 1 to 3 carbon atoms, more preferably a methylene group or an ethylene group, and even more preferably a methylene group.
[0068] When M is a pyridinium ion, examples of the substituent on the pyridine ring include a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom), a carboxy group, a linear or branched acyl group having 2 to 6 carbon atoms, a linear or branched alkyl group having 1 to 6 carbon atoms, a linear or branched alkoxy group having 1 to 6 carbon atoms, etc. M is an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + R 8 R 9 R 10 (wherein the symbols have the same meanings as above) is preferred. Examples of the alkali metal ion include a lithium ion, a sodium ion, a potassium ion, a rubidium ion, and a cesium ion. Examples of the alkaline earth metal ion include a calcium ion, a strontium ion, a barium ion, and a radium ion. R 8 , R 9 , and R 10 Examples of the organic group include the same as the substituents on the pyridine ring (excluding halogen atoms).
[0069] Among these, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 In terms of storage stability and color stability in the composition, a compound in which all of M are methyl groups is particularly preferred. n+ An example of this is Li + , Na + , K + , Ca 2+ , Mg 2+Examples of amines include ammonia, trimethylamine, diethylamine, dimethylaniline, ethylenediamine, triethanolamine, N,N-dimethylaminomethacrylate, N,N-dimethylaminobenzoic acid and its alkyl esters, N,N-diethylaminobenzoic acid and its alkyl esters, and N,N-bis(2-hydroxyethyl)-p-toluidine. 7 From the viewpoint of adhesion, p is preferably 1 or more, more preferably 2 or more, even more preferably 3 or more, and particularly preferably 4 or more; it is preferably 1000 or less, more preferably 100 or less, even more preferably 75 or less, and particularly preferably 50 or less.
[0070] Among these water-soluble acylphosphine oxides, the compound represented by the general formula (1) in which M is Li and the compound represented by the general formula (1) in which R 7 Particularly preferred is a compound represented by the general formula (2) synthesized from polyethylene glycol methyl ether methacrylate having a molecular weight of 950 corresponding to the group represented by the following formula:
[0071] The water-soluble acylphosphine oxides having such a structure can be synthesized according to known methods, and some of them are also available as commercial products. For example, they can be synthesized by the methods disclosed in JP-A-57-197289 and WO 2014 / 095724. The water-soluble photopolymerization initiator (D-1) may be used alone or in combination of two or more.
[0072] The water-soluble photopolymerization initiator (D-1) may be dissolved in the water on the surface of the tooth (wet body) and may selectively enhance the polymerization hardening property at the adhesive interface and inside the resin-impregnated layer, and may be dissolved in the dental composition or dispersed in powder form in the composition.
[0073] When the water-soluble photopolymerization initiator (D-1) is dispersed in powder form, if the average particle size is too large, it tends to settle, so it is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. On the other hand, if the average particle size is too small, the specific surface area of the powder becomes too large, and the amount dispersible in the composition decreases, so it is preferably 0.01 μm or more. That is, the average particle size of the water-soluble photopolymerization initiator (D-1) is preferably in the range of 0.01 to 500 μm, more preferably in the range of 0.01 to 100 μm, and even more preferably in the range of 0.01 to 50 μm.
[0074] The average particle size of each water-soluble photopolymerization initiator (D-1) powder can be calculated as the volume average particle size after performing image analysis using image analysis software (Mac-View; Mountec Co., Ltd.) on electron micrographs of 100 or more particles.
[0075] When the water-soluble photopolymerization initiator (D-1) is dispersed in powder form, the shape of the initiator may be, but is not particularly limited to, various shapes such as spherical, needle-like, plate-like, crushed, etc. The water-soluble photopolymerization initiator (D-1) can be prepared by a conventionally known method such as a pulverization method, a freeze-drying method, or a reprecipitation method, and from the viewpoint of the average particle size of the obtained powder, the freeze-drying method and the reprecipitation method are preferred, and the freeze-drying method (method 1) is more preferred.
[0076] The content of the water-soluble photopolymerization initiator (D-1) is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the total amount of polymerizable components in the dental composition from the viewpoint of the hardening property of the obtained dental composition, and more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass from the viewpoint of high initial adhesive strength and adhesive durability, and reduction of polymerization shrinkage stress. If the content of the water-soluble photopolymerization initiator (D-1) is less than 0.01 parts by mass, polymerization at the adhesive interface may not proceed sufficiently, resulting in a decrease in adhesive strength. On the other hand, if the content of the water-soluble photopolymerization initiator (D-1) is more than 20 parts by mass, if the polymerization performance of the water-soluble photopolymerization initiator (D-1) is low, sufficient adhesive strength may not be obtained, and further dissolution, dispersion, and diffusion in the dental composition may be insufficient.
[0077] · Non-water-soluble photopolymerization initiator (D-2) From the viewpoint of hardening, the dental composition of the present invention may contain, in addition to the water-soluble photopolymerization initiator (D-1), a water-insoluble photopolymerization initiator (D-2) having a solubility in water at 25°C of less than 10 g / L (hereinafter referred to as water-insoluble photopolymerization initiator (D-2)). The water-insoluble photopolymerization initiator (D-2) used in the present invention may be a known photopolymerization initiator. The water-insoluble photopolymerization initiator (D-2) may be used alone or in combination of two or more kinds.
[0078] Examples of the non-water-soluble photopolymerization initiator (D-2) include (bis)acylphosphine oxides, thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, and α-aminoketone compounds other than the water-soluble photopolymerization initiator (D-1).
[0079] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoyldi(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0080] Examples of the thioxanthones include thioxanthone, 2-chlorothioxanthen-9-one, and the like.
[0081] Examples of the ketals include benzyl dimethyl ketal and benzyl diethyl ketal.
[0082] Examples of the α-diketones include diacetyl, benzil, dl-camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzil, acenaphthenequinone, etc. Among these, dl-camphorquinone is particularly preferred from the viewpoint of having a maximum absorption wavelength in the visible light region.
[0083] Examples of the coumarin compound include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromo Coumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbo nylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylamino)coumarin, 3,Examples of the compounds include those described in JP-A-9-3109 and JP-A-10-245525, such as 3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.
[0084] Among the above-mentioned coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.
[0085] Examples of the anthraquinones include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.
[0086] Examples of the benzoin alkyl ether compound include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0087] Examples of the α-aminoketone compounds include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one.
[0088] Among these water-insoluble photopolymerization initiators (D-2), it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarin compounds, which provides a dental composition that is excellent in photocurability in the visible and near-ultraviolet regions and exhibits sufficient photocurability when using any of the light sources, such as a halogen lamp, a light-emitting diode (LED), and a xenon lamp.
[0089] The content of the water-insoluble photopolymerization initiator (D-2) is not particularly limited, but from the viewpoint of the curability of the obtained composition, the content of the water-insoluble photopolymerization initiator (D-2) is preferably in the range of 0.01 to 10 parts by mass, more preferably in the range of 0.05 to 7 parts by mass, and even more preferably in the range of 0.1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable components in the dental composition. If the content of the water-insoluble photopolymerization initiator (D-2) exceeds 10 parts by mass, if the polymerization performance of the polymerization initiator itself is low, there is a risk that sufficient adhesive strength cannot be obtained, and furthermore, there is a risk of precipitation from the dental composition.
[0090] The mass ratio of the water-soluble photopolymerization initiator (D-1) to the water-insoluble photopolymerization initiator (D-2) in the present invention [(D-1):(D-2)] is preferably 10:1 to 1:10, more preferably 7:1 to 1:7, even more preferably 5:1 to 1:5, and particularly preferably 3:1 to 1:3. If the water-soluble photopolymerization initiator (D-1) is blended in a mass ratio of more than 10:1, the hardening property of the dental composition itself may decrease, and it may be difficult to develop high adhesive strength. On the other hand, if the water-insoluble photopolymerization initiator (D-2) is blended in a mass ratio of more than 1:10, the hardening property of the dental composition itself may be increased, but the polymerization promotion at the adhesive interface may be insufficient, and it may be difficult to develop high adhesive strength.
[0091] [Chemical Polymerization Initiator] The dental composition of the present invention may further contain a chemical polymerization initiator, and an organic peroxide is preferably used. The organic peroxide used in the above-mentioned chemical polymerization initiator is not particularly limited, and known organic peroxides can be used. Representative organic peroxides include, for example, ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates. Specific examples of these organic peroxides include those described in International Publication No. 2008 / 087977.
[0092] [Polymerization accelerator (E)] In another embodiment, a polymerization accelerator (E) is used together with the water-insoluble photopolymerization initiator (D-2) and / or the chemical polymerization initiator. Examples of the polymerization accelerator (E) used in the present invention include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds.
[0093] The amines used as the polymerization accelerator (E) are divided into aliphatic amines and aromatic amines. Examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; and tertiary aliphatic amines such as N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, from the viewpoint of the hardening property and storage stability of the dental composition, tertiary aliphatic amines are preferred, and N-methyldiethanolamine and triethanolamine are more preferably used.
[0094] Examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, and N,N-diethyl-p -toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-(N,N-dimethylamino)ethyl benzoate, 4-(N,N-dimethylamino)methyl benzoate, 4-(N,N-dimethylamino)propyl benzoate, 4-(N,N-dimethylamino)n-butoxyethyl benzoate, 4-(N,N-dimethylamino)2-(methacryloyloxy)ethyl benzoate, 4-(N,N-dimethylamino)benzophenone, and 4-(N,N-dimethylamino)butyl benzoate. Among these, from the viewpoint of imparting excellent hardening properties to the dental composition, at least one selected from the group consisting of N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used.
[0095] Specific examples of sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds include those described in WO 2008 / 087977.
[0096] The polymerization accelerator (E) may be used alone or in combination of two or more. The content of the polymerization accelerator (E) used in the present invention is not particularly limited, but from the viewpoint of the hardening property of the obtained dental composition, it is preferably 0.001 to 30 parts by mass, more preferably 0.01 to 20 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable components in the dental composition. If the content of the polymerization accelerator (E) is less than 0.001 parts by mass, the polymerization may not proceed sufficiently, which may lead to a decrease in adhesiveness, and is more preferably 0.01 parts by mass or more. On the other hand, if the content of the polymerization accelerator (E) exceeds 30 parts by mass, if the polymerization performance of the polymerization initiator itself is low, there is a risk that sufficient adhesiveness cannot be obtained, and furthermore, there is a risk of precipitation from the dental composition, so it is more preferably 20 parts by mass or less.
[0097] [Filler (F)] Depending on the embodiment, the dental composition of the present invention may further contain a filler (F). The filler (F) is generally broadly classified into organic fillers, inorganic fillers, and organic-inorganic composite fillers. Examples of the organic filler material include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, crosslinked polymethyl methacrylate, crosslinked polyethyl methacrylate, polyamide, polyvinyl chloride, polystyrene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-styrene-butadiene copolymer, and these may be used alone or as a mixture of two or more. The shape of the organic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the obtained dental composition, the average particle size of the organic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm.
[0098] Examples of inorganic filler materials include quartz, silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, ytterbium oxide, and silica-coated ytterbium fluoride. These may also be used alone or in combination of two or more. The shape of the inorganic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the resulting composition, the average particle size of the inorganic filler is preferably from 0.001 to 50 μm, and more preferably from 0.001 to 10 μm.
[0099] Examples of the shape of the inorganic filler include amorphous fillers and spherical fillers. From the viewpoint of improving the mechanical strength of the composition, it is preferable to use a spherical filler as the inorganic filler. Furthermore, when the spherical filler is used, there is also an advantage that when the dental composition of the present invention is used as a self-adhesive dental composite resin, a composite resin excellent in surface smoothness can be obtained. Here, the spherical filler is a filler in which the particles observed in a unit field of view of the filler taken with an electron microscope are rounded, and the average uniformity obtained by dividing the particle diameter in the direction perpendicular to the maximum diameter by the maximum diameter is 0.6 or more. The average particle diameter of the spherical filler is preferably 0.05 to 5 μm. If the average particle diameter is less than 0.05 μm, the filling rate of the spherical filler in the composition may decrease, and the mechanical strength may be reduced. On the other hand, if the average particle diameter exceeds 5 μm, the surface area of the spherical filler may decrease, and the hardened dental composition having high mechanical strength may not be obtained.
[0100] In order to adjust the fluidity of the dental composition, the inorganic filler may be surface-treated with a known surface treatment agent such as a silane coupling agent before use, if necessary. Examples of such surface treatment agents include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, 11-methacryloyloxyundecyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0101] The organic-inorganic composite filler used in the present invention is obtained by adding a polymerizable compound to the inorganic filler described above in advance, forming a paste, polymerizing, and pulverizing it. As the organic-inorganic composite filler, for example, TMPT filler (trimethylolpropane methacrylate and silica filler mixed, polymerized, and pulverized) can be used. The shape of the organic-inorganic composite filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the obtained composition, the average particle size of the organic-inorganic composite filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm.
[0102] In this specification, the average particle size of the filler can be determined by a laser diffraction scattering method or by observing the particles with an electron microscope. Specifically, the laser diffraction scattering method is convenient for measuring the particle size of particles of 0.1 μm or more, and the electron microscope observation is convenient for measuring the particle size of ultrafine particles of less than 0.1 μm. 0.1 μm is a value measured by the laser diffraction scattering method.
[0103] Specifically, the laser diffraction scattering method can be performed by, for example, using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation) and measuring on a volume basis using a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.
[0104] Specifically, electron microscope observation can be performed by taking a photograph of the particles using an electron microscope (S-4000 model, manufactured by Hitachi, Ltd.) and measuring the particle diameters of the particles (200 or more) observed within a unit field of view of the photograph using image analysis type particle size distribution measurement software (Mac-View (Mountec Co., Ltd.)). At this time, the particle diameter is determined as the arithmetic mean value of the longest and shortest lengths of the particles, and the average primary particle diameter is calculated from the number of particles and their particle diameters.
[0105] In the present invention, two or more types of fillers having different materials, particle size distributions, and morphologies may be mixed or combined for use, and particles other than the filler may be unintentionally contained as impurities within a range that does not impair the effects of the present invention.
[0106] The content of the filler (F) used in the present invention is not particularly limited, and the filler (F) is preferably 0 to 2000 parts by mass relative to 100 parts by mass of the total amount of the polymerizable components in the dental composition. The suitable content of the filler (F) varies significantly depending on the embodiment in which it is used, so the suitable content of the filler (F) according to each embodiment will be shown together with the description of specific embodiments of the dental composition of the present invention described later.
[0107] [Fluoride ion releasing substances] The dental composition of the present invention may further contain a fluoride ion releasing substance. By blending the fluoride ion releasing substance, a dental composition capable of imparting acid resistance to tooth structure can be obtained. Examples of such fluoride ion releasing substances include metal fluorides such as sodium fluoride, potassium fluoride, sodium monofluorophosphate, lithium fluoride, and ytterbium fluoride. The above fluoride ion releasing substances may be used alone or in combination of two or more.
[0108] In addition, the dental composition may contain additives such as pH adjusters, polymerization inhibitors, thickeners, colorants, fluorescent agents, fragrances, and crosslinkers (e.g., polyvalent metal ion releasing components, etc.) within the range that does not inhibit the effects of the present invention. These may be used alone or in combination of two or more. The dental composition of the present invention may also contain antibacterial substances such as cetylpyridinium chloride, benzalkonium chloride, (meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxyhexadecylpyridinium chloride, (meth)acryloyloxydecylammonium chloride, and triclosan. The dental composition of the present invention may contain known dyes and pigments as colorants. Examples of polyvalent metal ion releasing components include metal ion releasing components belonging to Groups 3 and 13 of the periodic table. Examples of metals belonging to Group 3 of the periodic table include yttrium, scandium, and lanthanoids. Examples of metals belonging to Group 13 of the periodic table include aluminum, gallium, and indium. A preferred embodiment of the present invention is a dental composition that does not contain a crosslinking agent such as a polyvalent metal ion releasing component that forms an ionic crosslink with the monomer (B) having an acidic group, in order to appropriately lower the crosslink density in the polymer matrix and not impede the effect of reducing the polymerization shrinkage stress of the (meth)acrylic compound (A).
[0109] In the dental composition of the present invention, the content of other components other than the (meth)acrylic compound (A), the monomer (B) having an acidic group, the monomer (C) not having an acidic group, the polymerization initiator (D), the polymerization accelerator (E), the filler (F), the polymerization inhibitor, and the colorant is preferably less than 0.1% by mass, more preferably less than 0.01% by mass, and even more preferably less than 0.001% by mass. In addition, the dental composition of the present invention preferably has a polymerization shrinkage stress of less than 10 MPa, more preferably less than 9.5 MPa, and even more preferably less than 9.0 MPa. The method for measuring the polymerization shrinkage stress is as described in the Examples below.
[0110] The dental composition of the present invention can be used for dental treatment such as self-adhesive dental composite resin, dental bonding material, dental cement, pit and fissure sealant, loose tooth fixing material, orthodontic bonding material, and is preferably used as dental bonding material, self-adhesive dental composite resin, or dental cement. At this time, the dental composition of the present invention may be used as a two-bottle type or two-paste type in which the components are divided into two. The following is a specific embodiment of the application of the dental composition.
[0111] <Self-adhesive dental composite resin> One of the preferred embodiments of the dental composition of the present invention is a self-adhesive dental composite resin. When the dental composition of the present invention is used as a self-adhesive dental composite resin, it is preferable that the composition contains a (meth)acrylic compound (A), a monomer (B) having an acidic group, a monomer (C) having no acidic group, a polymerization initiator (D), a polymerization accelerator (E) and a filler (F). The polymerization initiator (D) is preferably a photopolymerization initiator, and more preferably contains a water-soluble photopolymerization initiator (D-1) and a water-insoluble photopolymerization initiator (D-2). When the dental composition of the present invention is used as a dental composite resin, a pretreatment material may be used, but since the dental composition has self-adhesiveness, the pretreatment material is not essential and the pretreatment material may not be used. A self-adhesive dental composite resin can be made by not containing a pretreatment material and only the dental composition of the present invention.
[0112] The content of each component in the self-adhesive dental composite resin, based on 100 parts by mass of the total amount of polymerizable components in the dental composition, preferably includes 0.1 to 30 parts by mass of the (meth)acrylic compound (A), 1 to 50 parts by mass of the monomer (B) having an acidic group, and 1 to 98 parts by mass of the monomer (C) not having an acidic group, more preferably includes 0.5 to 25 parts by mass of the (meth)acrylic compound (A), 1 to 80 parts by mass of the monomer (B) having an acidic group, and 5 to 95 parts by mass of the monomer (C) not having an acidic group, and even more preferably includes 1 to 20 parts by mass of the (meth)acrylic compound (A), 3 to 40 parts by mass of the monomer (B) having an acidic group, and 10 to 90 parts by mass of the monomer (C) not having an acidic group. Furthermore, the composition preferably contains 0.001 to 30 parts by mass of a polymerization initiator (D), 0.001 to 20 parts by mass of a polymerization accelerator (E), and 50 to 2,000 parts by mass of a filler (F) relative to 100 parts by mass of the total amount of the polymerizable components, and more preferably contains 0.05 to 10 parts by mass of a polymerization initiator (D), 0.05 to 10 parts by mass of a polymerization accelerator (E), and 100 to 1,500 parts by mass of a filler (F).
[0113] <Dental bonding material> Another preferred embodiment of the dental composition of the present invention is a dental bonding material. The dental bonding material can perform the demineralization step, the penetration step, and the curing step in one step. The dental bonding material may be a two-bottle type in which the first and second liquids are mixed just before use, or a one-bottle type in which one liquid can be used as is. Among them, the one-bottle type has a greater advantage in use because the process is more simplified. The dental bonding material may use a self-etching primer or the like as a pretreatment material. The dental composition used in the dental bonding material preferably contains a (meth)acrylic compound (A), a monomer (B) having an acidic group, a monomer (C) not having an acidic group, a polymerization initiator (D), a polymerization promoter (E), and a filler (F). The polymerization initiator (D) is preferably a photopolymerization initiator, and it is more preferable to use a water-soluble photopolymerization initiator (D-1) and a non-water-soluble photopolymerization initiator (D-2) in combination.
[0114] The content of each component in the dental bonding material is preferably 0.1 to 30 parts by mass of the (meth)acrylic compound (A), 1 to 90 parts by mass of the monomer (B) having an acidic group, and 1 to 98 parts by mass of the monomer (C) not having an acidic group, more preferably 0.5 to 25 parts by mass of the (meth)acrylic compound (A), 5 to 80 parts by mass of the monomer (B) having an acidic group, and 5 to 95 parts by mass of the monomer (C) not having an acidic group, and even more preferably 1 to 20 parts by mass of the (meth)acrylic compound (A), 5 to 70 parts by mass of the monomer (B) having an acidic group, and 10 to 90 parts by mass of the monomer (C) not having an acidic group, relative to 100 parts by mass of the total amount of polymerizable components in the dental composition. Furthermore, the composition preferably contains 0.001 to 30 parts by mass of a polymerization initiator (D), 0.001 to 20 parts by mass of a polymerization accelerator (E), and 0 to 100 parts by mass of a filler (F) relative to 100 parts by mass of the total amount of the polymerizable components, and more preferably contains 0.05 to 10 parts by mass of a polymerization initiator (D), 0.05 to 10 parts by mass of a polymerization accelerator (E), and 1 to 75 parts by mass of a filler (F).
[0115] <Dental cement> Another preferred embodiment of the dental composition of the present invention is a dental cement. Suitable examples of dental cement include resin cement, glass ionomer cement, and resin-reinforced glass ionomer cement. A self-etching primer may be used as a pretreatment material for the dental cement. When the dental composition of the present invention is used as a dental cement, it is preferable to include a (meth)acrylic compound (A), a monomer (B) having an acidic group, a monomer (C) having no acidic group, a polymerization initiator (D), a polymerization promoter (E) and a filler (F). The polymerization initiator (D) is preferably a chemical polymerization initiator, and more preferably a chemical polymerization initiator and a photopolymerization initiator are used in combination. The photopolymerization initiator is preferably a water-soluble photopolymerization initiator (D-1) and a non-water-soluble photopolymerization initiator (D-2) used in combination.
[0116] The content of each component in the dental cement, relative to 100 parts by mass of the total amount of polymerizable components in the dental composition, preferably includes 0.1 to 30 parts by mass of the (meth)acrylic compound (A), 1 to 50 parts by mass of the monomer (B) having an acidic group, and 1 to 98 parts by mass of the monomer (C) not having an acidic group, more preferably includes 0.5 to 25 parts by mass of the (meth)acrylic compound (A), 1 to 80 parts by mass of the monomer (B) having an acidic group, and 5 to 95 parts by mass of the monomer (C) not having an acidic group, and even more preferably includes 1 to 20 parts by mass of the (meth)acrylic compound (A), 3 to 40 parts by mass of the monomer (B) having an acidic group, and 10 to 90 parts by mass of the monomer (C) not having an acidic group. Furthermore, the composition preferably contains 0.001 to 30 parts by mass of a polymerization initiator (D), 0.001 to 20 parts by mass of a polymerization accelerator (E), and 50 to 2,000 parts by mass of a filler (F) relative to 100 parts by mass of the total amount of the polymerizable components, and more preferably contains 0.05 to 10 parts by mass of a polymerization initiator (D), 0.05 to 10 parts by mass of a polymerization accelerator (E), and 100 to 1,500 parts by mass of a filler (F).
[0117] The dental composition of the present invention may contain a solvent depending on the application. Examples of the solvent include water and organic solvents. As the organic solvent, known organic solvents can be used without any restrictions, and examples thereof include alcohol solvents (methanol, ethanol, 1-propanol, 2-propanol, etc.), acetone, methyl ethyl ketone, tetrahydrofuran, diethyl ether, diisopropyl ether, hexane, toluene, chloroform, ethyl acetate, butyl acetate, etc., and alcohol solvents are preferred. In an embodiment using an organic solvent, the content of the organic solvent is preferably 1 to 2000 parts by mass, more preferably 2 to 1000 parts by mass, and even more preferably 3 to 500 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable components. For example, when the dental composition of the present invention is used as a self-adhesive dental composite resin or dental cement, the dental composition may be a solvent-free dental composition. However, as long as it does not cause inconveniences such as poor curing or delayed curing, the inclusion of a small amount of water or organic solvent (for example, 3% by mass or less relative to the composition) is permitted. Therefore, some of the ingredients are sold in a form containing water or an organic solvent (e.g., colloidal silica), but in such cases, the water or organic solvent is removed to an acceptable limit before use in preparing the dental composition of the present invention.
[0118] In any of the preferred embodiments of the above-mentioned self-adhesive dental composite resin, dental bonding material, and dental cement, the content of each component can be appropriately changed based on the explanation in the above specification, and any component can be added, deleted, or otherwise modified.
[0119] The present invention includes embodiments in which the above configurations are combined in various ways within the scope of the technical concept of the present invention, as long as the effects of the present invention are achieved. EXAMPLES
[0120] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In addition, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention. The components used in the following examples and comparative examples, their abbreviations, structures, and test methods are as follows:
[0121] [(Meth)acrylic compound (A)] UN-7700: Urethane acrylate (manufactured by Negami Chemical Industries, Ltd., viscosity: 300,000 to 750,000 cps / 25°C, weight average molecular weight (Mw): 15,000 to 25,000, glass transition temperature (Tg): -41°C, polyester skeleton, number of acrylic groups: 2, weight average molecular weight per acrylic group: 7,500 to 12,500) UN-350: Urethane acrylate (manufactured by Negami Chemical Industries, Ltd., viscosity: ≧2,000,000cps / 25℃, weight average molecular weight (Mw): 12,500, glass transition temperature (Tg): -57℃, polyester skeleton, number of acrylic groups: 2, weight average molecular weight per acrylic group: 6,250) UN-353: Urethane acrylate (manufactured by Negami Chemical Industries, Ltd., viscosity: ≧2,000,000cps / 25℃, weight average molecular weight (Mw): 5,000, glass transition temperature (Tg): 10℃, polyester skeleton, number of acrylic groups: 2, weight average molecular weight per acrylic group: 2,500)
[0122] [(Meth)acrylic compounds] UN-2600: Urethane acrylate (manufactured by Negami Chemical Industries, Ltd., viscosity: 75,000-90,000cps / 25℃, weight average molecular weight (Mw): 2,500, glass transition temperature (Tg): -1℃, number of acrylic groups: 2, weight average molecular weight per acrylic group: 1,250) EBECRYL8807: Urethane acrylate (manufactured by Daicel Corporation, viscosity: 8,000cps / 60℃, weight average molecular weight (Mw): 1,000, glass transition temperature (Tg): 32℃, number of acrylic groups: 2, weight average molecular weight per acrylic group: 500)
[0123] [Monomer (B) having an acidic group and a molecular weight of less than 5000] MDP: 10-methacryloyloxydecyl dihydrogen phosphate
[0124] [Monomer (C) having no acidic group and having a molecular weight of less than 5000] D-2.6E: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average number of moles of ethoxy groups added: 2.6) DD: 1,10-decanediol dimethacrylate MAEA: N-methacryloyloxyethyl acrylamide
[0125] [Polymerization initiator (D)] Water-soluble photopolymerization initiator (D-1) Li-TPO: Lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (compound represented by the following formula (3)) [ka] · Non-water-soluble photopolymerization initiator (D-2) CQ: dl-camphorquinone
[0126] [Polymerization accelerator (E)] DABE: Ethyl 4-(N,N-dimethylamino)benzoate
[0127] [Filler (F)] Inorganic filler 1: Fine silica particles "Aerosil R 972" manufactured by Nippon Aerosil Co., Ltd., average particle size: 16 nm Inorganic filler 2: Silane-treated silica powder Silica powder (manufactured by Nichitsu Co., Ltd., product name: Hi-Silica) was pulverized in a ball mill to obtain pulverized silica powder. The average particle size of the obtained pulverized silica powder was measured using a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, model "SALD-2300") and found to be 2.2 μm. 100 parts by mass of this pulverized silica powder was surface-treated with 4 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated silica powder. Inorganic filler 3: Silane-treated barium glass powder Barium glass (manufactured by Estec Co., Ltd., product name "E-3000") was pulverized in a ball mill to obtain barium glass powder. The average particle size of the obtained barium glass powder was measured using a laser diffraction type particle size distribution measuring device (manufactured by Shimadzu Corporation, model "SALD-2300") and found to be 2.4 μm. 100 parts by mass of this barium glass powder was surface-treated with 3 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated barium glass powder.
[0128] 〔others〕 BHT: 2,6-di-t-butyl-4-methylphenol (stabilizer (polymerization inhibitor))
[0129] [Examples and Comparative Examples: Application of Dental Composition to Self-Adhesive Dental Composite Resin] <Examples 1 to 8 and Comparative Examples 1 to 4> Using the above-mentioned components, the components shown in Tables 1 and 2 were mixed and kneaded at room temperature to prepare the self-adhesive dental composite resins of Examples 1 to 8 and the dental composite resins of Comparative Examples 1 to 4. Next, the polymerization shrinkage stress, flexural modulus, flexural strength, and shear bond strength to enamel were measured using these self-adhesive dental composite resins according to the methods described below. Tables 1 and 2 show the compounding ratios (parts by mass) and test results of the self-adhesive dental composite resins of each Example and Comparative Example.
[0130] [Measurement of polymerization shrinkage stress] A stainless steel washer (inner diameter 5.3 mm × thickness 0.8 mm) coated with a release agent was placed on a 5.0 mm thick glass plate that had been sandblasted with 50 μm alumina powder, and the composite resin of each Example and Comparative Example was filled into the washer. Next, excess composite resin paste was removed, and the composite resin was sandwiched between a stainless steel jig (φ5 mm) that had been separately sandblasted and the glass plate.
[0131] The glass plate side of the sample was irradiated with light for 10 seconds using a dental LED light irradiator (manufactured by Morita Corporation, product name "Pencure 2000") to harden the composite resin, and the polymerization shrinkage stress at this time was measured using a universal testing machine (manufactured by Shimadzu Corporation). The measurement was performed three times, and the average value was taken as the polymerization shrinkage stress (N=3).
[0132] [Evaluation of bending properties] The strength was evaluated by a bending test in accordance with ISO4049:2009. Specifically, the procedure is as follows. The dental composition was filled into a SUS mold (length 2 mm × width 25 mm × thickness 2 mm), and the top and bottom (2 mm × 25 mm surfaces) of the dental composition (paste) were pressed with a glass slide. Next, the dental composition was cured by irradiating the front and back of the paste with light through the glass slide at five points on each side for 10 seconds using a dental LED light irradiator (Morita Corporation, Pencure 2000). The obtained cured product was subjected to a bending test using a universal testing machine (Autograph AG-I 100kN, Shimadzu Corporation) with a center distance of 20 mm and a crosshead speed of 1 mm / min, and the bending strength and bending modulus were measured, and the average values were shown in the table (N=5).
[0133] [Shear adhesion test to enamel] The labial surfaces of bovine mandibular anterior teeth were polished with #80 silicon carbide paper (Nihon Kenshi Co., Ltd.) under running water to expose the flat surface of the dentin to obtain samples. Tape was applied to the bottom surface of a 15-hole mold (Ultradent Co., Ltd., φ35 mm × height 25 mm), and the sample teeth were fixed on top of it. Plaster was filled into the mold and left to stand for about 30 minutes to harden the plaster. The samples were removed from the mold and polished with #600 silicon carbide paper (Nihon Kenshi Co., Ltd.) under running water until the adhesion surface was large enough (φ2.38 mm or more), and the adhesion surface was ultrasonically washed for 5 minutes.
[0134] A φ2.38 mm CR filling mold (Bonding Mold Insert, Ultradent) prepared separately was attached to a dedicated tool (Bonding Clamp, Ultradent). Next, the CR filling mold attached to the dedicated tool was lowered to fix the sample so that the CR filling mold was in close contact with the surface to be adhered. Next, the dental composite resin prepared in each Example and Comparative Example was thinly filled into the hole of the CR filling mold to a thickness of 1 mm or less. After that, the mold was filled again (up to about 2 / 3 of the mold, about 2 mm thick), and left for 10 seconds, and then the self-adhesive dental composite resin was cured by irradiating light with a dental LED light irradiator (Ultradent, product name "VALO") for 10 seconds. The sample was removed from the mold and used as a test sample for adhesion test. Next, the adhesion test sample was left in a thermostatic chamber set at 37°C for 24 hours while immersed in distilled water, and then removed and the adhesion strength was measured. The adhesion strength (shear adhesion strength) was measured by attaching the adhesion test sample to a dedicated holder (Test Base Clamp, Ultradent) and using a dedicated tool (Crosshead Assembly, Ultradent) and a universal testing machine (Shimadzu Corporation) with a crosshead speed set to 1 mm / min, and the average values are shown in the table (N=10).
[0135] [Table 1]
[0136] [Table 2]
[0137] As shown in Table 1, the self-adhesive dental composite resins according to the present invention (Examples 1 to 8) had a flexural strength of 80 MPa or more when cured and exhibited a low polymerization shrinkage stress of less than 10 MPa. In addition, in a shear adhesion test assuming a relatively deep cavity, they also exhibited a shear bond strength to enamel of 8 MPa or more. This result suggests that the inclusion of the (meth)acrylic compound (A) reduces the polymerization shrinkage stress, effectively reducing the risk of detachment and marginal leakage when a relatively deep cavity is repaired. In contrast, as shown in Table 2, the dental composite resins not containing the (meth)acrylic compound (A) according to the present invention (Comparative Examples 1, 3, and 4) had a polymerization shrinkage stress of 10 MPa or more, and it was confirmed that the reduction in polymerization shrinkage stress was insufficient and the shear bond strength to enamel was 7 MPa or less. In addition, it was confirmed that the dental composite resin not containing the monomer (B) having an acidic group (Comparative Example 2) had a shear bond strength to enamel of 1 MPa. [Industrial Applicability]
[0138] The dental composition according to the present invention is suitably used in the field of dentistry as a self-adhesive dental composite resin, a dental bonding material, or a dental cement.
Claims
1. The composition comprises a (meth)acrylic compound (A) having a weight average molecular weight of 5,000 to 50,000, a monomer (B) having an acidic group and a molecular weight of less than 5,000, a monomer (C) having no acidic group and a molecular weight of less than 5,000, and a polymerization initiator (D), wherein the weight average molecular weight per (meth)acrylic group of the (meth)acrylic compound (A) is 1,250 or more and less than 20,000, The (meth)acrylic compound (A) is a urethane-modified (meth)acrylic compound (A-1), the monomer (B) having an acidic group and a molecular weight of less than 5,000 contains a phosphate group- or pyrophosphate group-containing (meth)acrylic monomer, the content of the monomer (B) having an acidic group and having a molecular weight of less than 5,000 is in the range of 1 to 50 parts by mass per 100 parts by mass of the total amount of the polymerizable components in the dental composition; the monomer (C) having no acidic group and having a molecular weight of less than 5,000 contains a hydrophobic monomer (C-1) having no acidic group and having a molecular weight of less than 5,000; the content of the hydrophobic monomer (C-1) is in the range of 20 to 99 parts by mass relative to 100 parts by mass of the total amount of the polymerizable components in the dental composition; The polymerization initiator (D) contains a water-insoluble photopolymerization initiator (D-2) having a solubility in water at 25° C. of less than 10 g / L, A dental composition, comprising a non-water-soluble photopolymerization initiator (D-2) in an amount of 0.01 to 10 parts by mass relative to 100 parts by mass of the total amount of polymerizable components in the dental composition.
2. 2. The dental composition according to claim 1, wherein the content of the (meth)acrylic compound (A) is 0.1 to 30 parts by mass per 100 parts by mass in total of the (meth)acrylic compound (A), the monomer (B) having an acidic group, and the monomer (C) not having an acidic group.
3. 3. The dental composition according to claim 1, wherein the (meth)acrylic compound (A) has a viscosity at 25°C of 5,000 cps or more.
4. The dental composition according to any one of claims 1 to 3, wherein the (meth)acrylic compound (A) has a glass transition temperature (Tg) of 20°C or lower.
5. The dental composition according to any one of claims 1 to 4, wherein the (meth)acrylic compound (A) has a weight average molecular weight per (meth)acrylic group of 6,100 or more and less than 20,000.
6. The dental composition according to any one of claims 1 to 5, wherein the urethane-modified (meth)acrylic compound (A-1) is a (meth)acrylate having a urethane bond and a structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene.
7. The dental composition according to any one of claims 1 to 6, wherein the monomer (B) having an acidic group and a molecular weight of less than 5,000 contains a phosphate group-containing (meth)acrylic monomer.
8. The dental composition according to any one of claims 1 to 7, wherein the hydrophobic monomer (C-1) having no acidic group and a molecular weight of less than 5,000 contains an aliphatic compound-based bifunctional monomer.
9. The dental composition according to any one of claims 1 to 8, wherein the polymerization initiator (D) contains a water-soluble photopolymerization initiator (D-1) having a solubility in water at 25°C of 10 g / L or more and a water-insoluble photopolymerization initiator (D-2) having a solubility in water at 25°C of less than 10 g / L.
10. A self-adhesive dental composite resin comprising the dental composition according to any one of claims 1 to 9.
11. A dental bonding material comprising the dental composition according to any one of claims 1 to 9.
12. A dental cement comprising the dental composition according to any one of claims 1 to 9.
Citation Information
Patent Citations
Single-part, light-curable, self-adhering dental restorative composition
EP2153811A2
JP1975042696A
self-adhesive dental material
JP2004529946A
non-volatile dental composition
JP2006510583A
Hydroxy group-containing polymerizable compound and method for producing the same
JP2007217447A
Cited By
Liquid crystal composition and liquid crystal element
WO2023175978A1
